Increasing Revenue with New Source Engine Community-based (hyperlocal) business in the Open Banking era - Jadid Pratama Yuga Nugraha; Erma Suryani (Jurnal Indonesia Sosial Teknologi, 2024)
The high level of competition in the banking and non-bank industries makes banks have to continue to adapt in business to provide products and services to their consumers. Although the company recorded an encouraging performance and was able to maintain its position as a market leader, Bank BRI needed a business strategy to remain leading in revenue growth. This research aims to design a business dominance strategy and market share in the banking industry at BRI banks through a Dual Business approach that integrates ecosystem services (Hyperlocal Ecosystem) to increase competitiveness. The method used in this case study is qualitative descriptive with observation and in-depth interviews. The researcher conducted internal and external influence analysis using Porter's Five Forces Approach, Strategic Group Analysis, Value Chain Analysis, and Building Block Analysis to determine the positioning. In this study, the presence of a community-based business framework (hyperlocal business) is expected to add value-added banking services and increase revenue for BRI banks to be able to compete in the open banking industry. Based on the analysis of building blocks, the competitive strategy carried out by Bank BRI is differentiation where Bank BRI has the advantage of customer base as the main raw material in the community map, product quality, and innovation that cannot be imitated by its competitors.